Iron chelation increases the tolerance of Escherichia coli to hyper-replication stress - Charbon, Godefroid (Sci Rep, 2018)
In Escherichia coli, an increase in the frequency of chromosome replication is lethal. In order to identify compounds that affect chromosome replication, we screened for molecules capable of restoring the viability of hyper-replicating cells. We made use of two E. coli strains that over-initiate DNA replication by keeping the DnaA initiator protein in its active ATP bound state. While viable under anaerobic growth or when grown on poor media, these strains become inviable when grown in rich media. Extracts from actinomycetes strains were screened, leading to the identification of deferoxamine (DFO) as the active compound in one of them. We show that DFO does not affect chromosomal replication initiation and suggest that it was identified due to its ability to chelate cellular iron. This limits the formation of reactive oxygen species, reduce oxidative DNA damage and promote processivity of DNA replication. We argue that the benzazepine derivate (±)-6-Chloro-PB hydrobromide acts in a similar manner.